2014
DOI: 10.3892/br.2014.248
|View full text |Cite
|
Sign up to set email alerts
|

Association of methionine synthase rs1801394 and methionine synthase reductase rs1805087 polymorphisms with meningioma in adults: A meta-analysis

Abstract: Several epidemiological studies suggested that methionine synthase (MTRR) rs1801394 and methionine synthase reductase (MTR) rs1805087 polymorphisms may be involved in the risk of meningioma in adults; however, the results from different case-control studies have been inconsistent. Therefore, we performed a meta-analysis to investigate the association of MTRR and MTR polymorphisms with meningioma. PubMed, Web of Knowledge, China National Knowledge Infrastructure and Wanfang databases were searched up to October… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…Meanwhile, we observed that A66G variant was associated with increased meningioma and glioma susceptibility in Asian. Our results are consistent with a previous meta-analysis showing that MTRR rs1801394 polymorphism may increase the risk of meningioma [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, we observed that A66G variant was associated with increased meningioma and glioma susceptibility in Asian. Our results are consistent with a previous meta-analysis showing that MTRR rs1801394 polymorphism may increase the risk of meningioma [ 39 ].…”
Section: Discussionsupporting
confidence: 93%
“…The predominant genotype found in Japanese (Suzuki et al, 2008), Chinese (Yang et al, 2013) and African (Shi et al, 2003) population for MTRR A66G polymorphism is AA genotype (Table S5). We observed a decreased risk association for glioma with AG genotype of MTRR enzyme in our study population but no such association for glioma risk with AG genotype was observed in Chinese Han (Zeng et al, 2014;Zhang et al, 2013), British or European (Bethke et al, 2008) population. We did not observe any risk association for meningioma with MTRR A66G SNP in our study population but the Chinese Han population (Zhang et al, 2013) showed AG genotype of MTRR A66G as a risk factor for adult meningioma and a study in British population (Bethke et al, 2008) and meta-analysis in European population (Zeng et al 2014) showed homozygous polymorphism of MTRR GG genotype to be associated with increased risk for meningioma.…”
Section: Discussioncontrasting
confidence: 64%
“…We observed no significant association of increased risk for development of glioma or meningioma with MTR A2756G SNP. Other meta-analysis studies on European descent and Asian population also reported of no risk association with MTR A2756G for either with glioma or meningioma (Zeng et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Xu et al found that significantly increased meningioma risk was only observed under the TC vs CC model in a meta-analysis of four studies 9. A meta-analysis by Zeng et al showed that the MTRR rs1801394 polymorphism (seven case-control studies), but not MTR rs1805087 (seven case-control studies), may be associated with meningioma risk in adults 8. We removed data that did not meet the HWE, such as the rs1805087 data of Zhang et al,20 and added data from case-control studies, such as the WHO grade III meningioma group 21.…”
Section: Discussionmentioning
confidence: 99%
“…There were several previous meta-analyses for associations between meningioma risk and gene polymorphisms, including MTHFR rs1801133, MTRR rs1801394, MTR rs1805087, GSTM1 null/present, and GSTT1 null/present 8–13. However, an updated meta-analysis was still required.…”
Section: Introductionmentioning
confidence: 99%